Excitation spectrum of 10B nucleus when capturing real and virtual α-particles - Zhusupov, M.A.; Zhaksybekova, К.А.; Kabatayeva, R.S.; Kopenbayeva, A.S. (Recent Contributions to Physics, 2020)
In this paper within the multi-particle shell model the excitation spectra of 10B nucleus in lithium reactions of triton and a-particle clusters transfer were calculated using the summation of the corresponding spectroscopic S-factors. It is shown that the difference between excitation spectra of 10B nucleus in lithium reaction of a-cluster transfer and in the reaction of radiation capture 6Li(a, g)10B is due to the structural peculiarities of the states of 10В nucleus in near threshold region. In (a, g) reaction on 6Li nucleus the resonance structure of cross sections is observed. The observable resonances are due to small a-widths of the excited states of 10B nucleus. As the wave functions of the ground state of 6,7Li nuclei, as well as the ground and excited states of the 10B nucleus, we used the well-known wave functions of the many-particle shell model calculated at the Scientific Research Institute of Nuclear Physics, M. Lomonosov Moscow State University. The large escape of resonance monochromatic g-quanta with energy Eg = 5.1639 and Eg = 6.025 МэВ in the process on 6Li nucleus confirms the possibility of use of the reaction for diagnostics of fusion plasma by adding a definite amount of lithium isotopes into the plasma.